Market orientation and brand performance in Small and Medium Enterprises (SMES) in Malaysia context / Imelda Albert Gisip... [et al.] - Albert Gisip, Imelda; Dawayan, Cynthia; Ambad, Nabila Azwa; David, Jasmine; Olaybal, Delia L. (UiTM Cawangan Johor, 2019)
The focus of this study is to examine the impact of market orientation on brand performance of the Small Medium Enterprises (SMEs) in Malaysia context. Market orientation is identified as antecedent and critical for brand management success. This study is set as a cross sectional and quantitative study with sample size comprises 304 Malaysian SMEs from the food and beverage (F & B) manufacturing sector based on the list of Federation of Malaysian Manufacturers (FMM) directory 2012. Smart Partial Least Squared (PLS) version 2.0 software, a structural equation modelling technique was used to analyse data. Results of this study found that market orientation will not have a positive impact on brand performance of Malaysia’s SME despite several supporting empirical evidences on the direct relationship between market orientation and brand performance. This study enhances understanding on the brand management practices among Malaysian SMEs and may assist to formulate government support programs towards strengthening the brand-related knowledge and skills among the SMEs.